4) -9mx+8(3m-4)x+18-m egal36+6m, inlocuim pe x cu -3, astfel
-9m*(-3) + 8(3m-4)(-3) + 18 - m = 36 + 6m
27m -24 (3m-4) + 18 - m = 36 + 6m
27m - 72 m + 96 + 18 - m = 36 + 6m
-45m + 114 = 36 + 6m
-45 -6m - m= 36 - 114
-52m = 78
m = - 78/52 = -39/26 =- 3/2
SI CELELALTE SE FAC LA FEL. INLOCUIESTI PUR SI SIMPLU PE X CU NUMARUL DAT SI APOI IL AFLI PE M
9) 4(X+5) - 5(X+3) = X -5
4X + 20 - 5X -15 = X - 5
-X + 5 = X - 5
-X -X = -5 -5
-2X = -10
2X = 10
X = 5
B)4x+1+2(x-5) = 5(x+1)
4X + 1 + 2X -10 = 5X + 5
6X -9 = 5X + 5
6X - 5X = 9 + 5
X = 14
C) 2(x+3)-3(2x+1) = 8(2x-1)-9
2X + 6 - 6X -3 = 16X - 8 -9
-4X + 3 = 16 X -17
-4X - 16 X = -17 -3
-20X = -20
20X = 20
X = 20/20
X = 1
D) 3(2x+3)-2(3x+2) = -3(x+2)+2
6X + 9 - 6X - 4 = -3X -6 +2
5 = -3X -4
3X = -4 -5
3X = -9
X = -9/3
X = -3